IMPLEMENTASI INOVASI KETERAMPILAN MEMBACA PERMULAAN MELALUI MEDIA KARTU HURUF PADA ANAK KELAS II SDN BENDUNGAN 5 SRAGEN - Anatasya Putri Fortuna; Anggit Grahito Wicaksono; Mukhlis Mustofa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study describes the implementation of innovation in early reading skills throughthe use of letter card media for second grade students of SDN Bendungan 5 Sragen.This qualitative descriptive research involved teachers, students, and the principal.Data were collected through observation, interviews, and documentation, andanalyzed using Miles & Huberman’s model of data reduction, data display, andconclusion drawing. The findings show that letter card media effectively improvesstudents’ early reading skills, making them more active, enthusiastic, and confidentin recognizing letters, spelling, and reading simple words. Supporting factors includeteacher creativity, parental support, and a conducive learning environment, whilechallenges include varying student abilities, limited time, and different levels ofmotivation.